The evolution of Turkish-Russian relations in the 21st century: the potential for pragmatism - Baichorov, Aleksandr M.; Deniz, Ali Hazer (Journal of the Belarusian State University. International Relations, 2022)
The article presents an overview of the Turkish foreign policy strategy and its implications for the development of Turkish-Russian relations. The bilateral relationship is viewed in the context of the Turkish-Russian summit of 2021 which became an important landmark gave an impetus to the future growth of the Turkish-Russian relationship. The influence of the international context on the Turkish-Russian rapprochement is also addressed.
Keywords: Turkey; Russia; USA; EU; intentions; capabilities; economic projects; president V. Putin; president R. Erdogan; summit; Turkish-Russian relations; US-Turkish relations; Syria; Libya; South Caucasus; Black Sea; security